Total Immersion. - Verhagen, Marcus (Art Monthly, 2025)
The article discusses the emergence of vitalist art that presents itself to the viewer in the immediate present. It describes the use of light projection, interactive technology and computer graphics by artists to create immersive vitalist art. It explains the concept of techno-vitalism and its relation to phenomena that may be called immersive entertainments.